Gut-Brain Axis in the Early Postnatal Years of Life: A Developmental Perspective - Jena, Ankita; Montoya, Carlos A.; Mullaney, Jane A.; Dilger, Ryan N.; Young, Wayne; McNabb, Warren C.; Roy, Nicole C. (Frontiers in Integrative Neuroscience, 2020)
In the first two to three years of life, the development of the gastrointestinal (GI) tract and the brain in humans occurs in parallel. Emerging evidence suggests that alterations in the development of the GI tract during this critical period can influence brain development and vice-versa. It is increasingly recognized that communication between the GI tract and brain is mainly driven by neural, endocrine, immune, and metabolic mediators, collectively called the gut-brain axis (GBA). However, it is unclear whether changes in the GBA during the early postnatal period also occur in response to the parallel development of the GI tract and brain. This review summarizes the current understanding of the communication between the GI tract and brain in response to their development in the early postnatal period.